2016
DOI: 10.1063/1.4967518
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Probing the existence of partially arrested states in ionic liquids

Abstract: The recent predictions of the self-consistent generalized Langevin equation theory, describing the existence of unusual partially arrested states in the context of ionic liquids, were probed using all-atom molecular dynamics simulations of a room-temperature ionic liquid. We have found a slower diffusion of the smaller anions compared with the large cations for a wide range of temperatures. The arrest mechanism consists on the formation of a strongly repulsive glass by the anions, stabilized by the long range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…For the AA model, the MSD in the diffusive regime is higher for the cations than for the anions at low temperatures, whereas the discrepancy vanished at high temperatures. The observation that larger cations diffuse faster than smaller anions was recently attributed to the diffusion of cations through a glassy network of anions . For the CG model, the MSD in the diffusive regime is comparable for both ionic species, with a tendency for faster diffusion of cations at low temperatures and of anions at high temperatures.…”
Section: Resultsmentioning
confidence: 91%
“…For the AA model, the MSD in the diffusive regime is higher for the cations than for the anions at low temperatures, whereas the discrepancy vanished at high temperatures. The observation that larger cations diffuse faster than smaller anions was recently attributed to the diffusion of cations through a glassy network of anions . For the CG model, the MSD in the diffusive regime is comparable for both ionic species, with a tendency for faster diffusion of cations at low temperatures and of anions at high temperatures.…”
Section: Resultsmentioning
confidence: 91%
“…Further studies on charge transport showed the difference of RTILs to conventional electrolyte solutions [109] . Slower diffusion of smaller anions compared with large cations, were reported over a wide range of temperatures, i. e. formation of a strongly repulsive glass by the anions – termed arrested states [110] …”
Section: Resultsmentioning
confidence: 99%
“…In recent years, MD simulations have developed into a powerful tool for detailed studies on the structure and dynamics of ILs [18][19][20][21][22][23]. All-atom (AA) models not only revealed structural [20] and dynamical [18,[24][25][26] heterogeneity, but also yielded insights into their interplay [27,28]. However, such detailed atomistic modeling has also shortcomings.…”
Section: Introductionmentioning
confidence: 99%